EFEKTIVITAS PEMBENTUKAN KLASTER KERAJINAN LOGAM DALAM RANGKA MENINGKATKAN DAYA SAING (DESA CEPOGO KEC. CEPOGO, KAB. BOYOLALI) - , NIKEN PRADONAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Regional autonomy give a change regional to develop their regional appropriate their potential resource. Local economic development in Central Java supported by Central Java Governor design FPESD to form regional superior product based clustered.One of clusters is metal cfraft in Cepogo Village has dynamic development and ekspor scale. This research takes in Cepogo Village.This aims (a) to know character entrepreneur and cluster component,(b) to know efectivity of development cluster increased competitiveness industry, and (c)identify factor has corellation with metal craft cluster development.Reseach method used in this reaseach is qualitative quantitative method (mix method) by using the clusters approach.Sampling with survey.Data was collected through secondary data,questioner,and interview.Data was prosessing used likert scale and correlation.The analysis technique used is descriptive qualitative analysis. . The result of research is the demografis character of mikro,small and medium industry is not determined by education level,long effort and training participation.Take risk character of mikro,small and medium industry showed customer demand.Cluster component linkages with others.Efectivity cluster development showed that all factor has dominated by small industry.Wherease efectivity cluster development tends to be low for marketing indicator in mikro industry.While the factor that have strongest factor ad positive is supported and related industry for 0.782